2011
DOI: 10.5732/cjc.010.10592
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in the matrix metalloproteinase 2 promoter is closely associated with high risk of nasopharyngeal carcinoma in Cantonese from southern China

Abstract: Matrix metalloproteinase 2 (MMP2) has been shown to play an important role in several steps of cancer development. The -1306C/T polymorphism of the MMP2 gene displays a strikingly lower promoter activity than the T allele, and the CC genotype in the MMP2 promoter has been reported to associate with the development of several cancers. To assess the contribution of the MMP2 -1306C/T polymorphism to the risk of nasopharyngeal carcinoma (NPC), we conducted a case-control study and analyzed MMP2 genotypes in 370 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…For head and neck cancers, an inhibition of MMP-2 activity or synthesis also reportedly results in the suppression of metastasis of these tumors (Rosenthal et al, 2006;Chien et al, 2013). With regards to the pathogenesis of NPC, its association with MMP-2 is supported by a molecular epidemiological study which showed that the MMP-2 -1306C/T promoter polymorphism was associated with an increased risk of NPC, and enzyme linked immunosorbant assay studies which have shown that a high level of MMP-2 is associated with poor survival and high incidence of lymph node metastasis in these patients (Wong et al, 2004;Shao et al, 2011;Huang et al, 2013). We therefore investigated whether MMP-2 is involved in the antimetastatic activity of RIE on NPC cells.…”
Section: Discussionmentioning
confidence: 75%
“…For head and neck cancers, an inhibition of MMP-2 activity or synthesis also reportedly results in the suppression of metastasis of these tumors (Rosenthal et al, 2006;Chien et al, 2013). With regards to the pathogenesis of NPC, its association with MMP-2 is supported by a molecular epidemiological study which showed that the MMP-2 -1306C/T promoter polymorphism was associated with an increased risk of NPC, and enzyme linked immunosorbant assay studies which have shown that a high level of MMP-2 is associated with poor survival and high incidence of lymph node metastasis in these patients (Wong et al, 2004;Shao et al, 2011;Huang et al, 2013). We therefore investigated whether MMP-2 is involved in the antimetastatic activity of RIE on NPC cells.…”
Section: Discussionmentioning
confidence: 75%
“…Combined effect of > 3 MMP/TIMP variant containing genotypes imparted increased risk of GBC (P < 0.0001; [OR] =3. 36). Multivariate logistic regression results also supported association of MMP-2 (c.735C>T, c.1306 C>T), MMP-9 p.R668Q and TIMP2c.418G>C variants with GBC susceptibility.…”
mentioning
confidence: 58%
“…To date, several studies have evaluated genetic variation in MMP-2 in relation to cancer susceptibility but the results are conflicting. MMP-2 c.735 C>T polymorphism was found to be associated with lower risk in lung and oesophageal cancers (35) increased risk of nasopharyngeal carcinoma (36) but no association in hepatocellullar carcinoma (16). Similarly for MMP-2 c.1306 C>T, a large study showed this polymorphism to be associated with increased risk of breast cancer but effect was not significant (37).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the association between a polymorphism in the promotor region of MMP2 (SNP rs243865; nucleotide −1306) and NPC risk was evaluated in three independent populations. 27,28 In one study that included a discovery (593 cases and 480 controls) and a validation (239 cases and 286 controls) phase, evidence for an association between SNP rs243865 and NPC was reported. 28 This association was further reproduced in a separate study conducted among 370 NPC cases and 390 controls.…”
Section: Summary Of the Literaturementioning
confidence: 99%
“…28 This association was further reproduced in a separate study conducted among 370 NPC cases and 390 controls. 27 …”
Section: Summary Of the Literaturementioning
confidence: 99%